Rare case of hematometra in rudimentary horn of unicornuate uterus after tubal ligation - Sonawane, Pundalik; Waghela, Archana; Gaikwad, Supriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Congenital anomalies of the uterus and vagina are associated with a high incidence of infertility and multiple obstetric problems. Unicornuate uterus with rudimentary horn is a rare mullerian duct anomaly of female genital tract with incidence of 1/100000. It usually develops following insufficient development of mullerian ducts. These patients present with dysmenorrhea, dyspareunia, and chronic pelvic pain because of endometriosis and rarely with acute abdominal symptoms following distention and torsion of the non-communicating rudimentary horn. A case of a unicornuate uterus with non-communicating rudimentary horn with functional endometrium developing hematometra after tubal ligation is presented herein.